2012
DOI: 10.3126/kumj.v9i1.6265
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sniffing position and simple head extension for visualization of glottis during direct laryngoscopy.

Abstract: Background The ability of good glottis visualization during direct laryngoscopy is major determinant of easy tracheal intubation. Sniffing position for laryngoscopy is considered as gold standard and ideal position. Several studies have questioned the validation of sniffing potion. Objectives This study aims to compare relative efficacy of sniffing position and simple head extension for visualization of glottis during direct laryngoscopy. Methods Four hundred patients undergoing elective surgery under general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 10 publications
2
13
0
3
Order By: Relevance
“…The results of our study are supported by the studies of Singhal et al 14 , Adnet et al 15 , Bhattari et al 16 and Ambardekar et al 17 in terms of intubation difficulty score in two groups. All these studies suggest that sniffing position offers more ease of tracheal intubation than simple head extension.…”
Section: Jacksonsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of our study are supported by the studies of Singhal et al 14 , Adnet et al 15 , Bhattari et al 16 and Ambardekar et al 17 in terms of intubation difficulty score in two groups. All these studies suggest that sniffing position offers more ease of tracheal intubation than simple head extension.…”
Section: Jacksonsupporting
confidence: 90%
“…Bhattarai et al 16 in 2011 compared sniffing position with simple head extension for visualization of glottis during direct laryngoscopy in 400 patients. They found that glottis visualization is clinically better in sniffing position but not statistically significant (P value >0.05).…”
Section: Jacksonmentioning
confidence: 99%
“…After assessing the full text of these potentially useful studies, we included 6 studies with 2759 participants ( Fig. 1) [8,[13][14][15]23,24]. All 6 trials were prospective, randomized, and controlled, and provided data on glottic visualization and one or more data associated with intubation performance.…”
Section: Study Descriptionmentioning
confidence: 99%
“…All 6 trials were prospective, randomized, and controlled, and provided data on glottic visualization and one or more data associated with intubation performance. Each of 3 studies compared the success rate of intubation [14,15,24], the intubation time [15,23,24], and IDS score [8,13,15]. Four studies compared intubation in the SP to that in the simple head extension position, and 2 studies compared intubation in the SP to the so-called "ramp" position [23,24] (Table 1).…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation